ANALISA BAHAN SARANG BURUNG PECUK PADI HITAM {Phalacrocorax sulcirostris) di SUAKA MAGASATWA PULAU RAMBUT, TELUK JAKARTA - Aida Fithri (BERITA BIOLOGI, 2007)
The research was conducted from January 2002 to June 2003 at Pulau Rambut Wildlife Sanctuary Jakarta Bay. The objectives of this research were to explore the breeding strategy of Little Black Cormorant {Phalacrocorax sulcirostris) by analyzing their nest materials. The birds built their nest by using natural and unnatural materials. The shape and texture of nest material were rigid, rope-like and soft. The sources of nest material were trees, forest floor, beach, abandoned nest, aquatic plant living on the bottom of tbe sea, floating material from Java Island and fisherman activities at the sea surrounding Pulau Rambut Wildlife sanctuary.In addition they also collected nest materials by stealing from other nests, nest material carried by other flying individual, and from other individual floating on the sea while seizing the nest material in their beak. All nest materials were carried with their beak.Rigid materials were carried horizontally or diagonally and rope-like material were dorsally or ventrally.